2011
DOI: 10.3109/07420528.2011.574021
|View full text |Cite
|
Sign up to set email alerts
|

Varying the Length of Dim Nocturnal Illumination Differentially Affects the Pacemaker Controlling the Locomotor Activity Rhythm ofDrosophila Jambulina

Abstract: Photic entrainment of animals in the field is basically attributed to their exposure to the dimly lit nights flanked by the dawn and dusk twilight transitions. This implicates the functional significance of the dimly lit nights as that of the twilight transitions. Recently, the authors have demonstrated that the dimly lit night at 0.0006 lux altered the attributes of the circadian rhythm of locomotor activity of Drosophila jambulina. The present study examined whether the durations of such dimly lit nights aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The extremely short or long photoperiods are known to act as a weak zeitgeber, resulting in a poor entrainment, damping of the rhythm, arrhythmicity or miserable physiological performance in most attributes Thakurdas et al 2011;Sinam et al 2012). The results of the present study are in agreement with this hypothesis, as extremely short or extremely long photoperiods drastically reduced the fertility of D. biarmipes.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The extremely short or long photoperiods are known to act as a weak zeitgeber, resulting in a poor entrainment, damping of the rhythm, arrhythmicity or miserable physiological performance in most attributes Thakurdas et al 2011;Sinam et al 2012). The results of the present study are in agreement with this hypothesis, as extremely short or extremely long photoperiods drastically reduced the fertility of D. biarmipes.…”
Section: Discussionsupporting
confidence: 89%
“…Other than the photoperiod, the dark phase or scotoperiod of the entraining light-dark cycles may change the basic properties of the overt rhythms of Drosophila. For example, the dimly lit scotoperiod (9 to 15 h) selectively altered almost all attributes of the entrainment of the locomotor activity rhythm of the males of Drosophila jambulina and subsequent free-running rhythmicity of the locomotor activity rhythm of D. jambulina (Thakurdas et al 2011). Recently, it was elegantly demonstrated that the photoperiod had profound influence on the process of re-entrainment of the adult locomotor activity rhythm of Drosophila biarmipes, wherein the accelerating effects of the photoperiod had strong reliance on the direction of the shift of light-dark cycles (Sinam et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The broad spectrum (365–810 nm) white light obtained from the UV-free white light emitting diodes (6 VDC-0.02W, the angle of light emission 20–30°, Ligitek Electronics Co.) was used during the photophase at 300 lx as well as during the dim scotophase at 0.03 lx. The computerized photoelectric method for recording the adult locomotor activity rhythm of Drosophila has been described in details 2 , 15 , 22 . However, the method in brief is as follows.…”
Section: Methodsmentioning
confidence: 99%
“…In the same species, the nocturnal illumination at 0.0006 lx advanced the activity onset by several hours, extended the activity duration, enhanced the activity level and shortened the period of free-running rhythm 15 . Varying durations (9–15 h) of the dim scotophase at 0.0006 lx modulated the fundamental properties of the circadian pacemakers that controlled the adult locomotor activity rhythm of D. jambulina 2 . Dim nocturnal irradiance in D. melanogaster also advanced the morning peak but delayed the evening peak of activity that rendered the flies completely nocturnal 16 , 17 Moreover, it also altered the clock protein rhythms in the pacemaker neurons of the brain.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation